2014
DOI: 10.1071/sp14008
|View full text |Cite
|
Sign up to set email alerts
|

Surface ozone profiles at selected South Pacific sites

Abstract: Surface ozone profiles were studied at Fiji (18

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Analysis of 6 years (1997)(1998)(1999)(2000)(2001)(2002)(2003) of data from ozonesondes at four locations in the South Pacific has shown that, for the western Pacific, the seasonal displacement of the South Pacific Convergence Zone (SPCZ) is affecting transport patterns. Both photochemistry and transport patterns control the variability and seasonality in surface O 3 levels (Chandra et al, 2014). On the other hand, O 3 observations at the high-altitude (2.2 km) station of El Tololo in Chile have shown a clear increasing trend from 1995 to 2010 that is strongly related to stratospheric O 3 influx to the troposphere, with maxima in spring that are shifted during recent years to earlier times than before (Anet et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of 6 years (1997)(1998)(1999)(2000)(2001)(2002)(2003) of data from ozonesondes at four locations in the South Pacific has shown that, for the western Pacific, the seasonal displacement of the South Pacific Convergence Zone (SPCZ) is affecting transport patterns. Both photochemistry and transport patterns control the variability and seasonality in surface O 3 levels (Chandra et al, 2014). On the other hand, O 3 observations at the high-altitude (2.2 km) station of El Tololo in Chile have shown a clear increasing trend from 1995 to 2010 that is strongly related to stratospheric O 3 influx to the troposphere, with maxima in spring that are shifted during recent years to earlier times than before (Anet et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of 6-years (1997-2003) of data from ozonesondes at four locations in the south Pacific has shown that, for the Western Pacific, the seasonal displacement of the South Pacific Convergence Zone (SPCZ) is affecting transport patterns. Both photochemistry and transport patterns control the variability and seasonality in surface O3 levels (Chandra et al, 2014). On the other hand, O3 observations at high altitude (2.2. km) station of El Tololo in Chile have shown a clear increasing trend from 1995 to 2010 that is strongly related with stratospheric O3 influx to the troposphere, with maxima in spring that are shifted during recent years to earlier times than before (Anet et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Advection from the southern mid-latitudes introduces upper tropospheric and stratospheric ozone, along with emissions resulting from biomass burning. Being south of SPCZ, Fiji is more exposed to the latter (Chandra et al, 2014). According to Oltmans et al (2001), the impact of African wildfires is also prominent after August (Fig.…”
mentioning
confidence: 97%
“…8i). Moreover, the South Pacific Convergence Zone (SPCZ) nearby brings clean marine air to the upper troposphere (Chandra et al, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation